2020
DOI: 10.1186/s13018-020-02018-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate osteosynthesis (MIPO) versus open reduction and internal fixation (ORIF) in the treatment of distal fibula Danis-Weber types B and C fractures

Abstract: Background Minimally invasive plate osteosynthesis (MIPO) has been reported to be superior to open reduction and internal fixation (ORIF) in the treatment of different long bone fractures. Nevertheless, in distal fibula fractures, the evidence of MIPO remains scarce. The aim of this retrospective study was to compare the clinical and radiological outcomes of the minimally invasive techniques applied to the distal fibula with open reduction and internal fixation within a 12 months follow-up. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…This approach can minimize surgical trauma, alleviate postoperative pain, expedite the recovery process, and provide better cosmetic outcomes. 12 , 21 , 22 Indeed, research has shown that closed reduction is the greatest challenge in the MIPO technique. In addition, radiation exposure during the procedure is another factor that young orthopaedic physicians consider when opting for open reduction and internal fixation (ORIF) instead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can minimize surgical trauma, alleviate postoperative pain, expedite the recovery process, and provide better cosmetic outcomes. 12 , 21 , 22 Indeed, research has shown that closed reduction is the greatest challenge in the MIPO technique. In addition, radiation exposure during the procedure is another factor that young orthopaedic physicians consider when opting for open reduction and internal fixation (ORIF) instead.…”
Section: Discussionmentioning
confidence: 99%
“…MIPO technique, developed in the past 30 years, is considered because it most closely aligns with the concept of biologic internal fixation for fracture treatment, and it has found widespread application in treating fractures in various sites throughout the body, including the tibia, fibula, ulna, radius, humerus, clavicle, and scapula, among others. [9][10][11][12][13][14][15][16][17] The advantages of this technique include reducing iatrogenic damage to the soft tissues surrounding the fracture site and minimizing postoperative scar formation, thereby meeting patients' aesthetic requirements. 18,19 However, there are also some drawbacks associated with the MIPO technique in practical clinical operations.…”
mentioning
confidence: 99%
“…Malunion or delayed union are infrequent complications when using this type of implant in MIPO. Regarding infection rates, when MIPO and ORIF are compared, there is a lack of evidence in veterinary studies, but in the human side, evidence showed lower infection rates when MIPO techniques are used in long bone fractures [29,[60][61][62].…”
Section: Minimally Invasive Plate Osteosynthesismentioning
confidence: 99%
“…This allows secondary fracture healing with callus formation and preservation of the bone’s native blood supply and minimises wound related complications. MIPOtechniques have been shown to be superior to conventional osteosynthesis in the tibia and/or fibula, having lower rates of soft tissue related complications 5 . However, one of the challenges of MIPO is difficulty in assessing rotational profile of the limb during fixation.…”
Section: Introductionmentioning
confidence: 99%